Study on the Beneficial Impacts and Ethical Dimensions of Generative AI in Software Product Management - Gupta, Suneet; Sharma, Pragalbh; Chaudhary, Shweta; Kumar, Vinod; Singh, Surinder Pal; Lourens, Melanie; Beri, Nimisha (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The field of generative artificial intelligence (GAI) has advanced significantly in recent years, and its effects may be seen across the software product management industry. This comprehensive literature review draws on relevant studies published between 2016 and 2023 and demonstrates the possible uses, advantages, and restrictions of generative AI in this domain. The research demonstrates that technology aids in ideation, market research, consumer insights, spec writing, and product development. By automating tasks like code production and analysing user input, it may cut down on expensive and time-consuming software development. However, there are still concerns about the precision and safety of the technology, as well as ethical implications. Practical applications of generative AI have the potential to greatly enhance software product management processes, leading to more effective use of resources, higher quality product results, and enhanced user experiences.